(untitled) (Proceedings of the International Conference on Digital Health and Telemedicine, 2024)
The COVID-19 pandemic remarkably affects the world’s healthcare system. The healthcare service access and delivery system were affected worldwide. In the Philippines, hospitals nationwide defer non-urgent consults and rehabilitation services because of panic, fear, and anxiety about contracting the virus. Telerehabilitation services were implemented to meet the rehabilitation services gaps brought about by the pandemic in the community. This qualitative case study evaluates the implementation of Telerehabilitation services in a local community in the Philippines. A qualitative case study method was used as it utilized secondary data from audiovisual recordings, documents, and observations from Telerehabilitation sessions from Aug 2020 – May 2021. Thematic analysis identified four emerging themes regarding challenges experienced in the program implementation, namely, the technological factors, patient factors, approach and strategies, and infrastructure. At the same time, the lessons learned from the case study can be summed up into two themes: the value of partnership and bridging the gap. From the findings, a sustainable, effective, and safe digital physical therapy program can be established using the resources of both public and private organizations as its strength. This study can guide other local communities to establish a Telerehabilitation program to increase access to rehabilitation services using Public-Private Partnerships.